Iron-Induced Hepatocarcinogenesis—Preventive Effects of Nutrients - Tsuchiya, Hiroyuki (Frontiers in Oncology, 2022)
The liver is a primary organ that stores body iron, and plays a central role in the regulation of iron homeostasis. Hepatic iron overload (HIO) is a prevalent feature among patients with chronic liver diseases (CLDs), including alcoholic/nonalcoholic liver diseases and hepatitis C. HIO is suggested to promote the progression toward hepatocellular carcinoma because of the pro-oxidant nature of iron. Iron metabolism is tightly regulated by various factors, such as hepcidin and ferroportin, in healthy individuals to protect the liver from such deteriorative effects. However, their intrinsic expressions or functions are frequently compromised in patients with HIO. Thus, various nutrients have been reported to regulate hepatic iron metabolism and protect the liver from iron-induced damage. These nutrients are beneficial in HIO-associated CLD treatment and eventually prevent iron-mediated hepatocarcinogenesis. This mini-review aimed to discuss the mechanisms and hepatocarcinogenic risk of HIO in patients with CLDs. Moreover, nutrients that hold the potential to prevent iron-induced hepatocarcinogenesis are summarized.